2021
DOI: 10.1038/s41598-021-87626-9
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous nucleation on flat surface by depletion force in colloidal suspension

Abstract: Nucleation by sedimentation of colloidal particles on a flat surface is experimentally observed, and effect of attractive depletion force generated by polymers on nucleation is investigated. Sedimentation forms polycrystalline colloidal crystal on a flat surface, and above the threshold polymer concentration, ratio of the spontaneous nucleation increases, resulting in a decrease in the grain size, whereas dependence of the contact angle on the polymer concentration was not observed. We show that the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…My simulation results showed that the attractive interaction between particles and the wall needed to be greater than that between particles for the AB structure to be created on the wall. In a previous experiment 24 , in agreement with my simulations, the nucleation of colloidal crystals occurred first on a flat bottom wall during sedimentation, and the interaction between particles and the flat surface mainly affected the spontaneous nucleation. As shown in the supplementary, the interaction between particles and the wall are roughly twice as large as that between particles.…”
Section: Summary and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…My simulation results showed that the attractive interaction between particles and the wall needed to be greater than that between particles for the AB structure to be created on the wall. In a previous experiment 24 , in agreement with my simulations, the nucleation of colloidal crystals occurred first on a flat bottom wall during sedimentation, and the interaction between particles and the flat surface mainly affected the spontaneous nucleation. As shown in the supplementary, the interaction between particles and the wall are roughly twice as large as that between particles.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…The diamond and pyrochlore structures, which open up a complete three-dimensional photonic band gap, are obtained with the MgCu Laves phase, so that understanding the growth mechanism of these AB structures by binary colloidal crystals 14 , 20 is necessary to selectively create the MgCu Laves phase. Understanding the formation of good quality two-dimensional AB colloidal crystals is required because quality three-dimensional functional materials can be created more easily by using the two-dimensional crystals as substrates for epitaxial growth 21 24 rather than from free growth in an open three-dimensional space. Recently, the formation from solutions of a two-dimensional AB crystal on a wall was observed by experiment 25 .…”
Section: Introductionmentioning
confidence: 99%
“…2. Due to the relatively high monodisperisty of the particles, and the high Péclet number, the sediment shows a poly-crystalline structure, as observed in other experimental 19,20 or numerical 21 works.…”
Section: Experimental Set-upmentioning
confidence: 55%
“…However, the particles started to aggregate 47 beyond a certain concentration of NaPSS (∼>10 g/L), likely due to the depletion interaction. 48 At low concentrations (∼<0.05 g/L), the particles did not move at all. Based on the phase diagram of NaPSS, 49 the NaPSS solutions in our experiments are in the dilute regime.…”
Section: Resultsmentioning
confidence: 95%
“…For both molar masses, larger exclusion values were observed at higher mass concentrations of NaPSS. However, the particles started to aggregate beyond a certain concentration of NaPSS (∼>10 g/L), likely due to the depletion interaction . At low concentrations (∼<0.05 g/L), the particles did not move at all.…”
Section: Resultsmentioning
confidence: 99%